“This Is a Story about Regeneration”: Understanding The Missing: J. J. Macfield and the Island of Memories - McDivitt, Anne Ladyem (Eludamos: Journal for Computer Game Culture, 2021)
The Missing: J.J. Macfield and the Island of Memories (2018) is an intricate case of playing through an often grotesque and horrific game to develop empathy and understanding for the main character J.J. Macfield. The SWERY developed game involves physically dismembering the titular character to solve puzzles and move forward in her quest to locate her love interest, Emily. At first, it seems absurd and disturbing, but as the player moves through the game or reads the texts on J.J.’s phone, more of her story takes shape. There are odd moments such as a deer-headed character with a distorted voice indicating that there is a medical emergency, and they add to the sense of absurdity in a game that purposefully intends for you to harm your player character. The brutal mechanics are an integral part of J.J.’s journey and story. The game involves multiple suicides, bullying, self-harm, and ultimately, the revelation that the entire game is a narrative about a trans woman who has been in a dream while being revived by paramedics after a real-world suicide attempt. It’s a story of self-acceptance, of seeking the support of those closest to you, and by finishing game, J.J. is able to fight and conquer her self-loathing, represented by a monstrous being carrying a razorblade. J.J.’s physical pain and the body horror throughout the game represent the struggles that she has with body dysmorphia and her pain dealing with intolerance from her mother. This gameplay mechanic frames J.J.’s experiences in a way that is understandable even without her lived experience. I will argue that The Missing’s audio design and gameplay mechanics are integral to creating an empathetic playing experience. The game begins with the message, “this game was made with the belief that nobody is wrong for being what they are,” and that message is key to understanding The Missing: J.J. Macfield and the Island of Memories.